2021
DOI: 10.3390/ma14174774
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Microstructure and Properties of Duplex Stainless Steel Welds by Underwater Laser Welding with Different Shielding Gas

Abstract: Taking S32101 duplex stainless steel as the research object, underwater laser wire filling welding technology was used for U-groove filling welding. The influence of different shielding gas compositions on the ferrite content, microstructure, mechanical properties and pitting corrosion resistance was studied by simulating a water depth of 15 m in the hyperbaric chamber. The results show that, under the same process parameters, the size and proportion of austenite in the weld when using pure nitrogen as the shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In these processes, the loss of nitrogen will increase substantially. Wang et al [ 49 ] found that in the welding of lean duplex stainless steel (LDSS) S32101 using underwater laser welding, the size and percentage of austenite in the WZ and HAZ are higher when using pure nitrogen as the shielding gas compared to pure Ar or Ar–N 2 mixtures. The results of the mechanical evaluation allowed to observe that the welded joints exhibited higher strength and toughness compared to the base metal (BM), without the increase in N 2 in the Ar–N 2 mixture affecting these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In these processes, the loss of nitrogen will increase substantially. Wang et al [ 49 ] found that in the welding of lean duplex stainless steel (LDSS) S32101 using underwater laser welding, the size and percentage of austenite in the WZ and HAZ are higher when using pure nitrogen as the shielding gas compared to pure Ar or Ar–N 2 mixtures. The results of the mechanical evaluation allowed to observe that the welded joints exhibited higher strength and toughness compared to the base metal (BM), without the increase in N 2 in the Ar–N 2 mixture affecting these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Developments in marine engineering, aeronautics, space, transportation, and other industries greatly promoted the continuous development of welding technology. Enhancement of welding productivity to achieve welding automation and improve welding quality had become a crucial issue in the development of welding technology [1][2][3][4][5]. Twin-wire GMAW welding technology could achieve high speed welding and good deposition rate and so, had received much popularity as well as research attention at home and abroad [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [27] studied the microstructures and properties of DSS 2205 solid wire MIG welded samples prepared in different shielding gases, which were investigated for improving the weldability of the DSS 2205 welded joint, and the strength and corrosion resistance of welded joints were improved more obviously in a 98%Ar + 2%N2 mixed atmosphere. Wang et al [28] studied mixed shielding gas; increasing nitrogen had little effect on the strength and toughness of the weld. Regardless of the shielding gas used, the base metal was the weakest part of the weld.…”
Section: Introductionmentioning
confidence: 99%